2008
DOI: 10.1007/s00330-008-1054-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 1.0 M gadobutrol and 0.5 M gadopentate dimeglumine-enhanced MRI in 471 patients with known or suspected renal lesions: results of a multicenter, single-blind, interindividual, randomized clinical phase III trial

Abstract: The purpose of this phase III clinical trial was to compare two different extracellular contrast agents, 1.0 M gadobutrol and 0.5 M gadopentate dimeglumine, for magnetic resonance imaging (MRI) in patients with known or suspected focal renal lesions. Using a multicenter, single-blind, interindividual, randomized study design, both contrast agents were compared in a total of 471 patients regarding their diagnostic accuracy, sensitivity, and specificity to correctly classify focal lesions of the kidney. To test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Three of these studies, using MRA (4,6,10), showed no difference in qualitative parameters such as image quality or diagnostic confidence and only one found a higher SNR and CNR in favor of gadobutrol. The other two studies found no statistical advantage for the 1.0 M GBCA in terms of sensitivity, specificity and accuracy for lesion detection and characterization in patients with renal (14) or liver (15) cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Three of these studies, using MRA (4,6,10), showed no difference in qualitative parameters such as image quality or diagnostic confidence and only one found a higher SNR and CNR in favor of gadobutrol. The other two studies found no statistical advantage for the 1.0 M GBCA in terms of sensitivity, specificity and accuracy for lesion detection and characterization in patients with renal (14) or liver (15) cancer.…”
Section: Discussionmentioning
confidence: 94%
“…In abdominal dynamic MR angiography gadobutrol has superior contrast compared with 0.5 M GBCA [20]. Some publications report the use of gadobutrol for indications other than in CNS imaging and MR angiography [21,22]. Until now, no one has evaluated this Gd chelate in a direct comparison to another contrast agent for musculo-skeletal imaging purposes.…”
Section: Discussionmentioning
confidence: 95%
“…Quantitatively, the SNR and CNR for gadobenate dimeglumine and both standard and diluted forms of gadobutrol were significantly (p<0.02) higher than gadopentetate dimeglumine, yet no significant difference between either form of gadobutrol and gadobenate dimeglumine was reported. Overall, it seems that 1 M gadobutrol may or may not be advantageous for MRA compared with conventional Gd contrast agents, depending on the vascular territory being investigated [41,[59][60][61][62]65], but it has not demonstrated benefit beyond the higher relaxivity agents for CE-MRA [63,64].…”
Section: Effects Of High Field Mri On Pwi Qualitymentioning
confidence: 99%